2009
DOI: 10.1007/s11665-009-9398-6
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Shape Memory CuZnAl Open-cell Foam by Molten Metal Infiltration

Abstract: Foams and other highly porous materials with a cellular structure are known to have many interesting combinations of physical and mechanical properties. In addition, foaming of shape memory alloys (SMA) greatly improves the set of application possibilities. In this work an open-cell metal foam of a CuZnAl SMA is presented. This foam was produced through a recently proposed process, which consists mainly in molten metal infiltration of a bed of silica-gel particles and the subsequent use of hydrofluoric acid (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The resulting alloy specimens weighted around 80 g. By using these alloys as starting materials, foams were obtained by the method described in detail in Ref. [21,23]. Briefly, the alloys were re-melted in an open induction furnace using pure carbon crucibles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The resulting alloy specimens weighted around 80 g. By using these alloys as starting materials, foams were obtained by the method described in detail in Ref. [21,23]. Briefly, the alloys were re-melted in an open induction furnace using pure carbon crucibles.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, several studies aimed at finding suitable alloy candidates for producing structural SMFs are reported in the literature. The most promising involve the use of Fe-based [19] and Cu-based SMAs [20,21]. Among them, Cu-Zn-Al SMAs are of particular interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most innovative foaming process concerns the infiltration of leachable solid particles in the molten material [4][5][6]. In open literature, the most studied metallic foams, obtained by liquid infiltration of leachable space holders, are usually Al or Cu based alloys because these offer lightness, high stiffness, good thermal stability and quite low manufacturing cost [4].…”
Section: Introductionmentioning
confidence: 99%